2016
DOI: 10.1371/journal.pone.0161040
|View full text |Cite
|
Sign up to set email alerts
|

The Sulfamate Small Molecule CAIX Inhibitor S4 Modulates Doxorubicin Efficacy

Abstract: Carbonic anhydrase IX (CAIX) is a tumor-specific protein that is upregulated during hypoxic conditions where it is involved in maintaining the pH balance. CAIX causes extracellular acidification, thereby limiting the uptake of weak basic chemotherapeutic agents, such as doxorubicin, and decreasing its efficacy. The aim of this study was to determine if doxorubicin efficacy can be increased when combined with the selective sulfamate CAIX inhibitor S4. The effect of S4 on doxorubicin efficacy was tested in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This decrease in apoptosis was not caused by changes in the activity of active drug transporters because no changes in intracellular daunorubicin levels were observed, because changes were independent of the type of chemotherapeutic agent used, and because they were also seen in the absence of daunorubicin and cisplatin. In line with our results, the group of van Kuijk et al also found no enhanced doxorubicin efficiency in xenografts when CA IX activity was simultaneously blocked 41 . To further complicate matters, some chemotherapeutic agents, including cisplatin, seem to be able to block CA IX activity as well 44 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This decrease in apoptosis was not caused by changes in the activity of active drug transporters because no changes in intracellular daunorubicin levels were observed, because changes were independent of the type of chemotherapeutic agent used, and because they were also seen in the absence of daunorubicin and cisplatin. In line with our results, the group of van Kuijk et al also found no enhanced doxorubicin efficiency in xenografts when CA IX activity was simultaneously blocked 41 . To further complicate matters, some chemotherapeutic agents, including cisplatin, seem to be able to block CA IX activity as well 44 .…”
Section: Discussionsupporting
confidence: 93%
“…CA IX promotes extracellular acidification and stabilizes pH i in an acidic environment, and therefore the inhibition of CA IX in combination with the use of daunorubicin or cisplatin should increase the efficiency of chemotherapeutic drugs and restore chemosensitivity. Increased efficiency of chemotherapeutics in vitro, when administered together with inhibitors of CA IX, was recently described 41,42 . Furthermore, a cotreatment of HT-29 tumor-bearing mice with doxorubicin (which is a 14-hydroxylated version of daunorubicin) and CA IX inhibitors led to augmented chemosensitization and reduced tumor growth 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic switch towards increased glycolysis in hypoxic environments also affects the ability of these cells to survive therapy. For instance, the enhanced glycolytic rate increases the intracellular amounts of lactate and CO 2 , which are transported out of the cell, contributing to an extracellular acidic pH [16] and an increased therapy resistance [17]. The substantial increase of lactate production during hypoxia allows the scavenging of reactive oxygen species (ROS) molecules generated after radiation exposure due to the antioxidant properties of lactate [18].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the acetazolamide-induced intensification of DOX treatment in CA IX-rich cell lines reported by Gieling et al (vide supra), Kuijk and colleagues performed a followon study by using an isoform-selective CA IX inhibitor S4 [74]. This ureido-substituted sulfamate SLC-0111 analog has been earlier described to exert significant antiproliferative efficacy in vitro in different breast cancer tumor models [75,76].…”
Section: S4 and Doxorubicinmentioning
confidence: 99%